Nicolas Lémery (1645-1715) and his Physical-chemical Theory about Different Phenomena for Earth Sciences - Cándido Manuel GARCÍA CRUZ (Cuadernos Dieciochistas)
An unabridged translation of a work of Nicolas Lémery (1645–1715) is presented for the first time in Spanish, wherein this French chemist and apothecary attempts an explanation on physical and chemical basis of several significant phenomena in Earth Sciences, such as earthquakes, subterranean fires, hurricanes, lightning and thunder. This explanation had a common cause for all the aforementioned phenomena: the processes of mineral fermentation, in this case of sulfur and iron, as a heat source, within the corpuscular theory of matter and mechanistic philosophy, and likewise it represents an interesting contribution of the influence of chemistry on the incipient development of experimental geology at the dawn of the 18th Century.